Tamoxifen Twists Again: On and Off-Targets in Macrophages and Infections - Sfogliarini, Chiara; Pepe, Giovanna; Dolce, Arianna; Della Torre, Sara; Cesta, Maria Candida; Allegretti, Marcello; Locati, Massimo; Vegeto, Elisabetta (Frontiers in Pharmacology, 2022)
Beyond the wide use of tamoxifen in breast cancer chemotherapy due to its estrogen receptor antagonist activity, this drug is being assayed in repurposing strategies against a number of microbial infections. We conducted a literature search on the evidence related with tamoxifen activity in macrophages, since these immune cells participate as a first line-defense against pathogen invasion. Consistent data indicate the existence of estrogen receptor-independent targets of tamoxifen in macrophages that include lipid mediators and signaling pathways, such as NRF2 and caspase-1, which allow these cells to undergo phenotypic adaptation and potentiate the inflammatory response, without the induction of cell death. Thus, these lines of evidence suggest that the widespread antimicrobial activity of this drug can be ascribed, at least in part, to the potentiation of the host innate immunity. This widens our understanding of the pharmacological activity of tamoxifen with relevant therapeutic implications for infections and other clinical indications that may benefit from the immunomodulatory effects of this drug.